Noise Cancellation for HIPERLAN/2 with Open Loop Transmit Diversity Technique - Maan A. Yahya; Omar Ibrahim Alsaif; Ibrahim Ahmed Saleh; Ahmed M. Abdulkhaleq; Naser Ojaroudi Parchin; Yasir I. A. Al-Yasir; Raed A. Abd-Alhameed (Inventions, 2019)
A new proposed method is presented, where multiple antennas have been applied into HIPERLAN/2 system in addition to employing space-time diversity technique, especially the Alamouti technique. The suggested approach is used to cancel or reduce the effect of the transmitted power using a feedback signal process within the transceiver unit, especially when the antennas are closely located and working in full-mode duplexing. Several parameters including the transmitted power, the received power, and the feedback accuracy have been considered for testing the performance of the system in term of the signal to noise ratio (SNR) versus bit error rate (BER). A software programme using MATLAB and Simulink is implemented to evaluate the proposed method. The results showed that the system performance is heavily dependent on the amount of the mismatch in the feedback, the received power, and the transmitted power. The performance of the system decreases as the feedback accuracy increases when the transmitted power and the received power are constant. At the same time, the performance of the system decreases as the transmitted power increases when the received power and the mismatch are constant. Finally, the increase in the received power enhances the system performance when the other parameters are constant.